Comparative immunogenicity analysis of intradermal versus intramuscular immunization with a recombinant human adenovirus type 5 vaccine against Ebola virus - Zhang, Zhe; Zhao, ZhengHao; Wang, Yudong; Wu, Shipo; Wang, Busen; Zhang, Jinlong; Song, Xiaohong; Chen, Yi; Lv, Peng; Hou, Lihua (Frontiers in Immunology, 2022)
The proper route for vaccine delivery plays an important role in activating a robust immune response. Several viral vector-based vaccines against Ebola disease administered intramuscularly have been found to have excellent immunogenicity and protectiveness. In this study, we evaluated different vaccine routes for Ad5-EBOV delivery by comparing humoral and cellular responses, germinal center reactions, dendritic cell activation and antigen expression. Mice injected intramuscularly with the vaccine exhibited an advantage in antigen expression, leading to more robust germinal center and humoral responses, while intradermal injection recruited more migrating DCs and induced a more polyfunctional cellular response. Our study provides more data for future use of viral vector-based vaccines.